Changes in accumulation‐area firn stratigraphy and meltwater flow during a period of climate warming: Devon Ice Cap, Nunavut, Canada. Issue 4 (14th November 2013) - Gascon, Gabrielle; Sharp, Martin; Burgess, David; Bezeau, Peter; Bush, Andrew B. G.
Abstract [1] To document climate‐driven changes in firn stratigraphy and their implications for meltwater flow patterns within firn on the Devon Ice Cap, Nunavut, during the 21st century summer warming, 500 MHz ground‐penetrating radar (GPR) surveys were conducted along a 40 km transect in each spring from 2007 to 2012. These linear GPR surveys were supplemented by four 190 m by 100 m GPR grid surveys and 36 firn cores. Increased meltwater percolation and infiltration ice formation associated with high surface melt rates since 2005 modified the firn stratigraphy substantially over a horizontal distance of nearly 30 km. The most dramatic change involved the growth of a thick ice layer within the firn body. This layer grew primarily by upward accretion over an initial widespread ice layer formed during summer 2005. It thickened by between 0.5 and 4.5 m over the study period and filled much of the pore volume in the upper part of the firn, reducing vertical percolation of meltwater into deeper sections of the firn and thus the water storage potential of much of the firn reservoir. Heterogeneous percolation of surface meltwater promoted by rolling topography played an important role in meltwater infiltration and drainage, encouraging lateral flow at the tops of small hills and ponding and refreezing of meltwater beneath surface depressions.